2022
DOI: 10.7324/japs.2022.121104
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of gallic acid-loaded PLGA hydrogel as teat sealant for preventing mastitis in dry cows

Abstract: Mastitis or bovine mastitis is an inflammation of the mammary teat caused by an infection. To control mastitis during the dry period, an internal teat sealant was prepared and characterized by encapsulating gallic acid (GA), an antibacterial compound, into an in situ poly(lactic-co-glycolic acid) (PLGA) hydrogel. GA-loaded internal hydrogel teat sealants (IHTSs) were successfully formed in phosphate buffer saline at a 1% weight ratio of GA in a 39% weight ratio of PLGA vehicle. GA was entrapped in the matrix o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Gallic acid has demonstrated safety in cell culture and animal models, as evidenced by many studies ( 17 , 28 , 29 ). In our research, gallic acid exhibited cell viability exceeding 70% when tested on milk phagocytes, thereby establishing the safety level of gallic acid, particularly at a concentration of 50 μM applied to milk phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid has demonstrated safety in cell culture and animal models, as evidenced by many studies ( 17 , 28 , 29 ). In our research, gallic acid exhibited cell viability exceeding 70% when tested on milk phagocytes, thereby establishing the safety level of gallic acid, particularly at a concentration of 50 μM applied to milk phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…150 The study conducted by Baipaywadi et al, 2022, suggested that Gallic acid loaded PLGA hydrogel can be used as a teat sealant for preventing mastitis in dry cows. 151 …”
Section: Current Preventive Methodsmentioning
confidence: 99%
“…In order to measure the absorbance at 570 nm, a 96-well ELISA plate reader was used. The percentage of cells in the positive control group that were absorbed (100 percent alive) was utilized to determine the cells' vitality [ 35 ].…”
Section: Methodsmentioning
confidence: 99%